Interplanetary spacecraft navigation using pulsars - Deng, X.; Hobbs, G.; You, X.; Li, M.; Keith, M.; Shannon, Ryan; Coles, W.; Manchester, R.; Zheng, J.; Yu, X.; Gao, D.; Wu, X.; et al. (2013)
We demonstrate how observations of pulsars can be used to help navigate a spacecraft travelling in the solar system. We make use of archival observations of millisecond pulsars from the Parkes radio telescope in order to demonstrate the effectiveness of the method and highlight issues, such as pulsar spin irregularities, which need to be accounted for. We show that observations of four millisecond pulsars every seven days using a realistic X-ray telescope on the spacecraft throughout a journey from Earth to Mars can lead to position determinations better than ~20 km and velocity measurements with a precision of ~0.1 ms−1.